Tinggalan Cagar Budaya dalam Akulturasi Budaya Tionghoa di Kota Sibolga - Rudiansyah Rudiansyah (Studi Budaya Nusantara, 2021)
The title of this research is 'Remains of Cultural Heritage in Acculturating Chinese Culture in Sibolga city'. The purpose of this study is to find out how Chinese culture can integrate with coastal communities in Sibolga. The culture that develops can generally be witnessed in various ceremonial ceremonies carried out, such as traditional ceremonies, weddings, celebrations of historic days, festivals, and others. This study uses a descriptive method with a qualitative approach. Qualitative research is expected to produce an in-depth description of speech, writing, and the observable behavior of an individual, group, and society. This study using the basis of acculturation theory. The results of the study indicate that there are inter-community groups that have different cultures, unite and change in nature, so that they become a unique cultural blend, and blend harmoniously.Keywords: heritage; acculturation; Sibolga; public; Chinese